2022
DOI: 10.3389/fmars.2021.770543
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of COVID-19 on the Catch of Small-Scale Fishers and Their Families Due to Restriction Policies in Davao Gulf, Philippines

Abstract: COVID-19 was declared a global pandemic by the World Health Organization in 2020 with countries putting up several measures to mitigate and flatten the curve of hospitalizations and death from travel bans to home confinements and local lockdowns. This pandemic created health and economic crises, leading to increased incidence of poverty and food crisis especially on both agriculture and the fisheries in many developing nations including the Philippines. The specific objectives of this study were to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Aside from this, farmers were affected by the COVID-19 pandemic which limits them from getting more income. The same was true with the shrimp vendors who encountered difficulties selling their shrimp harvests for the reason of less buyers and less mobility due to the pandemic [56,57]. The shrimps from the farms were sold at lesser prices and this was not good for the farmers because their investments cannot be recouped when prices were down.…”
Section: Conclusion and Recommendationmentioning
confidence: 91%
See 1 more Smart Citation
“…Aside from this, farmers were affected by the COVID-19 pandemic which limits them from getting more income. The same was true with the shrimp vendors who encountered difficulties selling their shrimp harvests for the reason of less buyers and less mobility due to the pandemic [56,57]. The shrimps from the farms were sold at lesser prices and this was not good for the farmers because their investments cannot be recouped when prices were down.…”
Section: Conclusion and Recommendationmentioning
confidence: 91%
“…These are relevant issues that the government should look into, provide alternative livelihoods for the affected fish farmers, and help them to adapt to the possible impacts of climate change, the pandemic and give them additional financial support as well as trainings and seminars on how to adapt to the challenges that they might encounter in their aquaculture [18,56]. Also the government should help provide access to export markets and processing firms so that the farmers do not need to worry on disposing and selling their seafood products [2].…”
Section: Conclusion and Recommendationmentioning
confidence: 99%
“…Within the study area itself, mobility restriction showed as the main health protocol during the pandemic that negatively affect aquaculture farm as well as market disruption that hampered their marketing operations [64,65]. Though in some commercial farms that have some access to the market, they are less affected by market disruption.…”
Section: Preprintsmentioning
confidence: 97%
“…Accumulated pollution from watershed activities and from self-generated organic load has resulted in slower growth of shrimp, higher susceptibility to diseases, and the worst is mass mortalities [60].Presence of disease in populations and ecosystems is influenced by numerous environmental factors, including infectious organisms mostly viruses, pollutants such as chemical and biological wastes, and deficiency in essential nutrients [29]. COVID-19 restrictions and its severe economic impact [13,63,64,65].…”
Section: Preprintsmentioning
confidence: 99%
“…COronaVIrus Disease (COVID-19) pandemic [1] that began in Wuhan, China in December 2019 has reached over 74 million confirmed cases over the globe by 11 June 2021 [2] and has been declared a global pandemic by WHO on 11 March 2020 [3] , [4] . Ongoing efforts to curb the spread of the pandemic have dramatically disrupted the well-being and livelihoods of billions of people globally [5] .…”
Section: Introductionmentioning
confidence: 99%